The dust content of high-z submillimeter galaxies revealed by Herschel - Santini, P; Maiolino, R; Magnelli, B; Silva, L; Grazian, A; Altieri, B; Andreani, P; Aussel, H; Berta, S; Bongiovanni, A; Brisbin, D; Calura, F; et al. (2010)
We use deep observations taken with the Photodetector Array Camera and Spectrometer (PACS), on board the Herschel satellite as part of the PACS evolutionary probe (PEP) guaranteed project along with submm ground-based observations to measure the dust mass of a sample of high-z submillimeter galaxies (SMGs). We investigate their dust content relative to their stellar and gas masses, and compare them with local star-forming galaxies. High-z SMGs are dust rich, i.e. they have higher dust-to-stellar mass ratios compared to local spiral galaxies (by a factor of 30) and also compared to local ultraluminous infrared galaxies (ULIRGs, by a factor of 6). This indicates that the large masses of gas typically hosted in SMGs have already been highly enriched with metals and dust. Indeed, for those SMGs whose gas mass is measured, we infer dust-to-gas ratios similar or higher than local spirals and ULIRGs. However, similarly to other strongly star-forming galaxies in the local Universe and at high-z, SMGs are characterized by gas metalicities lower (by a factor of a few) than local spirals, as inferred from their optical nebular lines, which are generally ascribed to infall of metal-poor gas. This is in contrast with the large dust content inferred from the far-IR and submm data. In short, the metalicity inferred from the dust mass is much higher (by more than an order of magnitude) than that inferred from the optical nebular lines. We discuss the possible explanations of this discrepancy and the possible implications for the investigation of the metalicity evolution at high-z. © 2010 ESO.